Cognitive function during acute exercise: A test of the transient hypofrontality theory - Del Giorno, J. M.; Hall, E. E.; O'Leary, K. C.; Bixby, W. R.; Miller, P. C. (Journal of Sport & Exercise Psychology, 2010)
The purpose of this study was to test the transient hypofrontality theory (Dietrich, 2003) by examining the influence of exercise intensity on executive control processes during and following submaximal exercise. Thirty participants (13 female) exercised for 30 min at ventilatory threshold (VT) or at 75% of VT. The Contingent Continuous Performance Task (CPT) and Wisconsin Card Sorting Test (WCST) were used as measures of executive control. They were administered before, during, immediately following, and 20 min after exercise. An increase in false alarms and unique errors (p = .05) occurred during both conditions. False alarms for the CPT and total and perseverative errors for the WCST remained elevated immediately following exercise at VT, but not at exercise below VT (p = .01). The decreased executive control function during exercise can be explained by the transient hypofrontality theory. Following VT, executive control performance remained poor possibly owing to an additional amount of time the brain needs to return to homeostasis following intense exercise.